Relationship between Body Mass Index and Articular Injuries Accompanying Primary Anterior Cruciate Ligament Tear in Male Knees: A Retrospective Observational Study - Ulusoy, Gökhan Ragıp; Kızılgöz, Volkan; Sivrioğlu, Ali Kemal (The Journal of Knee Surgery, 2019)
The objective of this study was to determine the effects of body mass index (BMI), as a modifiable risk factor, on meniscal, chondral, and ligamentous injuries, as well as on bone marrow edema accompanying anterior cruciate ligament (ACL) rupture. This retrospective observational study analyzed 84 male patients who underwent primary ACL reconstruction from 2015 to 2018. Magnetic resonance imaging was performed within 6 weeks of injury. Bone bruise, tendon, ligament, meniscal, and muscle injuries were evaluated. The surgery was performed within 3 months after the injury. Detailed arthroscopic findings (chondral, meniscal, and ligamentous injuries) were documented intraoperatively. The weight and height were used to quantify BMI (weight in kg/height in m2). Of the 84 male patients, 58 had associated articular injuries. The median age of the study population was 24 years (minimum: 17 years, maximum: 43 years) years. The mean BMI, height, and weight were 27.12 ± 0.78 kg/m2, 1.73 ± 0.01 m, and 81.17 ± 21.52 kg, respectively. The relationship between higher BMI and associated articular injuries (95% confidence interval [CI]) was statistically significant (p < 0.001). There was a statistically significant relationship between weight and associated articular injuries (p = 0.003). Height and age were not predictive factors. Higher BMI and weight were significant risk factors for associated articular injuries in the presence of ACL tear. Height was not found to be a predictive factor. Higher BMI was associated with increased risk of medial and/or lateral meniscus tears and bone bruising.
Keywords: anterior cruciate ligament; body mass index; bone marrow edema